2015
DOI: 10.1002/glia.22938
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone activation of retinoic acid synthesis in hypothalamic tanycytes

Abstract: Thyroid hormone (TH) is essential for adult brain function and its actions include several key roles in the hypothalamus. Although TH controls gene expression via specific TH receptors of the nuclear receptor class, surprisingly few genes have been demonstrated to be directly regulated by TH in the hypothalamus, or the adult brain as a whole. This study explored the rapid induction by TH of retinaldehyde dehydrogenase 1 (Raldh1), encoding a retinoic acid (RA)‐synthesizing enzyme, as a gene specifically express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 67 publications
(109 reference statements)
3
20
0
Order By: Relevance
“…In F344 rats, this includes retinoic acid signalling genes and proteins involved in uptake (Stra6, Ttr and Crbp1), synthesis (Raldh1, Raldh2), receptor response (RAR) and ligand clearance (Crapb1 and Cyp26B1). 54 Consistent with this, T3 Crpb1, Crabp2, RAR and RXR are all strongly regulated by photoperiod, with high expression under long days and much reduced expression under short days.…”
Section: The Role Of the Retinoic Acid Systemsupporting
confidence: 65%
See 1 more Smart Citation
“…In F344 rats, this includes retinoic acid signalling genes and proteins involved in uptake (Stra6, Ttr and Crbp1), synthesis (Raldh1, Raldh2), receptor response (RAR) and ligand clearance (Crapb1 and Cyp26B1). 54 Consistent with this, T3 Crpb1, Crabp2, RAR and RXR are all strongly regulated by photoperiod, with high expression under long days and much reduced expression under short days.…”
Section: The Role Of the Retinoic Acid Systemsupporting
confidence: 65%
“…54 In F344 rats, the large changes in Raldh1 mRNA seen in response to photoperiod leads to an increase in tissue levels of retinoic acid in the hypothalamus. 54 In F344 rats, the large changes in Raldh1 mRNA seen in response to photoperiod leads to an increase in tissue levels of retinoic acid in the hypothalamus.…”
Section: The Role Of the Retinoic Acid Systemmentioning
confidence: 99%
“…Previous studies have shown the importance of local synthesis of both TH and RA within the HVZ of the hypothalamus to the photoperiodic response24 and recent work has revealed that TH regulates the expression of Raldh1 suggesting that TH drives the photoperiodic response at least in part through RA signalling9 (Fig. 7).…”
Section: Discussionmentioning
confidence: 91%
“…Ex-vivo hypothalamic slice cultures were set up as previously described9. Slices were treated for 48 hrs with 1 μM RA or an equivalent concentration of DMSO (0.1%) diluted in culture medium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation